The Profession of IT Voices of Computing. - Denning, Peter J. (Communications of the ACM, 2008)
The author laments the seemingly widespread perception that computer science and computer programming are essentially the same thing. In the public eye programming is an inflexible, rote undertaking with limited career opportunities. Moreover many are content to be simply users of technology, and cannot see much appeal in learning how to create it . In fact, computer science extends well beyond programmng to embrace a number of disciplines including mathematics, engineering, science, and algorithm design.